BELA PASIR (Belajar Mengenal Laut, Pantai, dan Pesisir): Edukasi Bagi Generasi Muda Pesisir Landangan - Anita Diah Pahlewi; Creani Handayani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
As a coastal village, Landangan has fishery resource management activities. Due to pandemic Covid-19 situation, children who go to school must be able to access the internet to participate in learning activities. Children are increasingly attached to their gadgets. This causes the child to be indifferent to the surrounding environment. They become less interested in learning about fisheries, marine and coastal areas because of the lack information about maritime and maritime-based approaches. The purpose of this community service is to introduce and transfer the knowledge about the coast and the sea. The method used in this community service is consists of several stages, namely the initial survey, socialization, action, monitoring and evaluation. The presenters explained topics related to the potential and opportunities of marine resources, especially in Situbondo Regency. The participants were also go to the beach for beach cleaning-up activities. Participants gain a lot of insight and knowledge from the presentation of the material. Besides, they also learn to have more intention about their marine environment through beach clean-up activities, because their coastal village is a valuable asset. As suggestions, the other training activities need to be held to continue this community service for improving the knowledge and capabilities of human resources in Landangan Village.